Population genomics meet Lagrangian simulations: Oceanographic patterns and long larval duration ensure connectivity among Paracentrotus lividus populations in the Adriatic and Ionian seas. Issue 8 (14th March 2017) - Paterno, Marta; Schiavina, Marcello; Aglieri, Giorgio; Ben Souissi, Jamila; Boscari, Elisa; Casagrandi, Renato; Chassanite, Aurore; Chiantore, Mariachiara; Congiu, Leonardo; Guarnieri, Giuseppe; Kruschel, Claudia; Macic, Vesna; et al.
Abstract: Connectivity between populations influences both their dynamics and the genetic structuring of species. In this study, we explored connectivity patterns of a marine species with long‐distance dispersal, the edible common sea urchin Paracentrotus lividus, focusing mainly on the Adriatic–Ionian basins (Central Mediterranean). We applied a multidisciplinary approach integrating population genomics, based on 1, 122 single nucleotide polymorphisms (SNPs) obtained from 2b‐RAD in 275 samples, with Lagrangian simulations performed with a biophysical model of larval dispersal. We detected genetic homogeneity among eight population samples collected in the focal Adriatic–Ionian area, whereas weak but significant differentiation was found with respect to two samples from the Western Mediterranean (France and Tunisia). This result was not affected by the few putative outlier loci identified in our dataset. Lagrangian simulations found a significant potential for larval exchange among the eight Adriatic–Ionian locations, supporting the hypothesis of connectivity of P. lividus populations in this area. A peculiar pattern emerged from the comparison of our results with those obtained from published P. lividus cytochrome b (cytb) sequences, the latter revealing genetic differentiation in the same geographic area despite a smaller sample size and a lower power to detect differences. The comparison with studies conducted using nuclear markers on other species with similar pelagic larval durations in the same Adriatic–Ionian locations indicates species‐specific differences in genetic connectivity patterns and warns against generalizing single‐species results to the entire community of rocky shore habitats. Abstract : 2b‐RAD and Lagrangian simulations were used to explore connectivity in the sea urchin Paracentrotus lividus . We detected genetic homogeneity in the Adriatic–Ionian basins, and weak but significant differentiation respect to samples from France and Tunisia. Lagrangian simulations found a significant potential for larval exchange among the eight Adriatic–Ionian locations, supporting the view of connectivity of P. lividus populations in this area. Our results, based on more than 1, 000 polymorphic SNPs, contrast with the strong differences in mtDNA frequencies, recently reported for the Adriatic and Ionian seas. Our results add a strong reason of caution for conclusions on genetic differentiation based only on mtDNA markers, at least in this species.